Inverted J-Shaped Association of High-Sensitivity C-Reactive Protein with the Levels of Serum Uric Acid: Cross-Sectional and Longitudinal Analyses - Liu XZ; Tian YJ; Fan J; Liu LY (Dove Medical Press, 2022)
Xing Zhen Liu,1,* Ya Jun Tian,1,* Jie Fan,2 Lian Yong Liu3 1Department of Health Management, Hangzhou Aeronautical Sanatorium for Special Service of China Air Force, Hangzhou, People's Republic of China; 2Department of Traffic Management Engineering, Zhejiang Police College, Hangzhou, People's Republic of China; 3Department of Endocrinology, Punan Hospital of Pudong New District, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Jie FanZhejiang Police College, No. 555 Binwen Road, Binjiang District, Hangzhou, People's Republic of China, Tel +8613567198867, Fax +8657131161558, Email fanjie@zjjcxy.cnLian Yong LiuDepartment of Endocrinology, Punan Hospital of Pudong New District, No. 279 Linyi Road, Pudong, Shanghai, 200336, People's Republic of China, Tel +8613564144866, Fax +862158892708, Email chinallu@163.com